Cooperative Herbal Medicine Manufacturing Training Save Business (KSU) Munyai Mekhawan Labuhan Mandi Village, West Coast Districts, Lampung Province - Septa Riadi; Dwi Eva Nirmagustina; Husna Purnama (International Journal of Social Service and Research, 2022)
Pekon Labuhan Mandi on the West Coast, many store the potential of medicinal plants that can be utilized. So that Sang Bumi Ruwa Jurai University implements a community service program through a mentoring method that will be organized by the Faculty of Economics, Sang Bumi Ruwa Jurai University with the target of KSU munyai mekhawan Labuhan Mandi members and the Mandi Labuhan community who contribute to the manufacture of herbal medicine, especially the women's business group processing herbs. (Spice) in the form of training activities. From the results of these activities, it can be concluded that the implementation of this training received a positive and enthusiastic response from the KSU Muway Mekhawan member group because of the increased knowledge possessed by the usah group, and the hassle to be developed and become additional household income. Based on the activities that have been done, Pengabdi hopes that there will be other community service programs that can increase community income through household businesses.